A study on the proficiency of archivists in Metro Manila - Reyes, Raymond M.
The importance, power, and values that archives hold demand qualified and competent archivists to handle them. To determine the qualified and competent archivists, it is imperative to measure their proficiency against the competency standards. Ensuring that archivists are proficient enough is a way to make sure that archives are well-protected and their power not abused.